2012
DOI: 10.1590/s0102-86502012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the damage caused by clamping or section of cervical sympathetic nerve in rabbits

Abstract: PURPOSE: To study the macro and microscopic evaluation of the damage caused by clamping or section of cervical sympathetic nerve in rabbits, quantifying the collagen in the lesions. METHODS: Twenty rabbits were divided into two groups of ten, doing in group 1 (section) section of the right cervical sympathetic nerve, while in group 2 (clipping) clipping of the nerve. All rabbits were induced to death on the seventh day after surgery. The macroscopic variables were: consequences of nerve lesion, clip appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Marinho Jr. et al 14 and Arantes-Marinho 2 also demonstrated a deposit of collagen in area of sympathetic nerve damage, with predominance of type I collagen in relation to type III, even in the early stage.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Marinho Jr. et al 14 and Arantes-Marinho 2 also demonstrated a deposit of collagen in area of sympathetic nerve damage, with predominance of type I collagen in relation to type III, even in the early stage.…”
Section: Discussionmentioning
confidence: 89%
“…Marinho Jr. et al 14 did not identify significant differences in the inflammatory process caused by the clipping of the sympathetic nerve compared to the one with its section. However, due to the absence of continuity lesion observed by the clipping lesion, they suggested that studies on the inflammatory process at different periods after the removal of the compressive effect of the clipping could demonstrate a possible involution of the inflammatory process, associated or not to anatomofunctional regeneration.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations